Description of Nurse's Attitude in Caring for Violent Behavior Patients - Ashar Ariandi; Rusli Abdullah; Basmalah Harun; Ekayanti H. Ahmad; Ricky Zainuddin (Newinera Publisher, 2022)
Predisposing factors become the cause of violent behavior originating from clients such as lack of attention which usually occurs in childhood, having low emotional abilities such as someone who is easily angry, has anxiety disorders, depression, family relationships that are not going well, losing someone beloved. While precipitation factors such as hopelessness, helplessness, and lack of confidence. Interviews and observations are the methods used in this study. The attitude of nurses in caring for patients with violent behavior is included in the good category (82.5%) as evidenced by the score on the interview sheet. Based on the results of observations regarding the attitude of nurses in caring for patients with violent behavior, nurses have carried out in accordance with the theory based on the level of attitude as evidenced by the interview sheet.